Luxmeter Equipped with Proximity Sensor for Operating Lamp Light Calibration in Hospital - Levana Forra Wakidi; Lusiana Lusiana; Lamidi Lamidi; Artdieansyah Nur Wiaam; Isaac John Ibanga (Jurnal Teknokes, 2022)
The measurement of the operating lamp light on the operating table is very necessary so that the light rays do not glare during surgery and pathological conditions can be recognized easily without any shadows. This study aims to design a tool to measure light intensity equipped with automatic distance measurement. The design of this tool uses an ultrasonic sensor HC-SR04 to measure the distance between the light source and the sensor module and the MAX44009 sensor to measure the light intensity of the operating lamp displayed on the TFT screen. The design of the tool has been tested on operating lamps. In this study, measurements were made on two light sources, namely the GEA brand operating lamp in the Operating Room RSIA Putri Surabaya and lamps in an Electromedical Engineering Workshop on the Surabaya campus. The results of measurements when using a lamp in an electromedical engineering workshop in Surabaya with the distance between the module and the light source using a 75 cm roll meter, it is known that the error value is 0.0127% for a distance of 100 cm as much as 0.0045%. The module error value when measuring the intensity of light between the tool and the lamp in the electromedical engineering workshop with a roll meter distance setting of 75 cm gets an error value of 0.082% lux and at a roll meter distance of 100 cm, the lux error value is 0.055%. The design of a lux meter that is equipped with a proximity sensor can measure the intensity of light and the distance between the device and the light source and can assist in the learning process with a more effective Luxmeter design that will help Electromedical Technician in testing operating lamps in hospitals become more efficient